A Comparative Study of Inhibitive Effects of Some Schiff Bases on Mild Steel in Acidic Media by Mass Loss Techniques - Abha Goyal; V. K. Swami; S. P. Mathur (E-Journal of Chemistry)
Mass loss techniques have been employed to study the corrosion inhibition of some newly synthesized Schiff bases. viz. N-4-(Diethyl amino) salicylidine-2-amino-5-chloropyridine (SB1), N-(4-ethylbenzalidine)-2-amino-5-chloropyridine (SB2), N-(4-ethylbenzalidine)-2-amino-5-bromopyridine (SB3), N-4-(Diethyl amino) salicylidine-2-amino-5-bromopyridine (SB4) for mild steel in HCl and H2SO4 solutions. Results of inhibition efficiencies from the mass loss technique show that Schiff bases are good inhibitors in both the acidic solutions. Inhibition efficiencies increase with the increase in the concentration of acids as well as those of inhibitors. Maximum efficiency for H2SO4 was found 99.78% and for HCl it was 97.92%.